WITHDRAWAL SYNDROME IN THE NEONATAL CONTEXT - Petricio Martins, Karoline; da Rocha Nascimento Pereira, Rosenilda; de Matos Sales, Letícia; Gonçalves dos Santos, Jucelene; Machado, Elizeu; Maria Principe Crucinsky, Viviane; Mayara Leandro Alves, Georgia; Pereira da Silva, Ivana; José dos Santos Cardoso, Maria; Milack, Cilmara (Health and Society, 2024)
The use, throughout the gestational period, of legal and illicit drugs, such as alcohol, tobacco and other substances, exposes babies to neurosubstances, which can cause risks to the mother and the fetus. The relevance of improving knowledge, on the part of health professionals, about SAN is therefore observed, enabling its early and correct identification and appropriate treatment. Therefore, the objective of this study is to analyze the withdrawal syndrome in the neonatal context. To this end, a narrative review study was carried out using articles available in the Lilacs and MedLine, Scielo and PUBMed databases, using original and free online scientific articles, in Portuguese, English and Spanish. Therefore, in the end, 17 articles were included in the present review. It is noted that SAN is a relevant disease for newborns, as it can lead to significant repercussions on the individual’s development and cause lifelong consequences, causing microcephaly, seizures, respiratory problems and the like. Because of this, health professionals must have technical-scientific knowledge to quickly identify the signs and symptoms presented by the newborn, implementing strategies and appropriate care to minimize injuries and reverse possible symptoms.